Improving safe post-abortion care practices: A study on interventions implemented by Ipas Pakistan - Arshad, Amna; Aziz, Hina; Shabbir, Ghulam; Shakya, Sagun; Munir, Zarnab (Frontiers in Public Health, 2023)
An estimated fifty million induced abortions occur in developing countries annually, and an estimated seven million women are treated for complications associated with unsafe abortions. Postabortion care (PAC) is an integrated service delivery model that includes both maternal health and family planning interventions. This study aims to examine improvement in safe post-abortion care practices implemented at the public level facilities through an integrated PAC model aligned with WHO recommendations. It was a descriptive study utilizing data of 27616 PAC clients recorded and reported by the providers on the logbooks from 113 selected public health facilities from March 2018- December 2021 in Islamabad capital territory, Punjab, Sind, and Khyber Pakhtunkhwa provinces of Pakistan. Women who received PAC services of age more than 25 years 22652 (82%), with a mean age of 29 + 5 years. Most of these women were in their first trimester 26,110 (95%) and majorly diagnosed with PAC (incomplete, missed, or threatened) 26,838 (97%). The majority of women 25,324 (92%) received safe methods for post-abortion care which included the use of Misoprostol 15,804 (58%) and Manual vacuum aspiration 8,898 (32%). 72% of women opted for a contraceptive method that included Long-acting reversible contraceptives (10%), short-term excluding condoms (27%), and condoms (34%). The key predictors identified for uptake of the post-abortion family planning method indicated that women more than 25 years of age, in the early second trimester, and who were counseled on post-abortion family planning were more likely to adopt the contraceptive method compared to others. Increased access to post-abortion care & post-abortion family planning could potentially reduce the incidence of unsafe abortion, unintended pregnancies, and associated maternal mortality. The experience of Pakistan suggests that the integrated post-abortion care service delivery model can be effectively implemented within the public health system.